Endocrine Pancreas in Cats With Diabetes Mellitus. (January 2016) - Zini, E.; Lunardi, F.; Zanetti, R.; Heller, R. S.; Coppola, L. M.; Ferro, S.; Guscetti, F.; Osto, M.; Lutz, T. A.; Reusch, C. E.; Cavicchioli, L.
Pancreatic amyloidosis and loss of α and β cells have been shown to occur in cats with diabetes mellitus, although the number of studies currently available is very limited. Furthermore, it is not known whether pancreatic islet inflammation is a common feature. The aims of the present study were to characterize islet lesions and to investigate whether diabetic cats have inflammation of the pancreatic islets. Samples of pancreas were collected postmortem from 37 diabetic and 20 control cats matched for age, sex, breed, and body weight. Histologic sections were stained with hematoxylin and eosin and Congo red; double labeled for insulin/CD3, insulin/CD20, insulin/myeloperoxidase, insulin/proliferating cell nuclear antigen, and glucagon/Ki67; and single labeled for amylin and Iba1. Mean insulin-positive cross-sectional area was approximately 65% lower in diabetic than control cats ( P = .009), while that of amylin and glucagon was similar. Surprisingly, amyloid deposition was similar between groups ( P = .408). Proliferation of insulin- and glucagon-positive cells and the number of neutrophils, macrophages, and T (CD3) and B (CD20) lymphocytes in the islets did not differ. The presence of T and B lymphocytes combined tended to be more frequent in diabetic cats ( n = 8 of 37; 21.6%) than control cats ( n = 1 of 20; 5.0%). The results confirm previous observations that loss of β cells but not α cells occurs in diabetic cats. Islet amyloidosis was present in diabetic cats but was not greater than in controls. A subset of diabetic cats had lymphocytic infiltration of the islets, which might be associated with β-cell loss.